Đề bài : Cho 3 số x,y,z thoả mãn điều kiện \(\frac{y+z-x}{x}=\frac{z+x-y}{y}=\frac{x+y-z}{z}\). Tính giá trị biểu thức \(A=\left(1+\frac{x}{y}\right)\left(1+\frac{y}{z}\right)\left(1+\frac{z}{x}\right)\)
GIẢI :
Ta có : \(\frac{y+z-x}{x}=\frac{z+x-y}{y}=\frac{x+y-z}{z}\Leftrightarrow\frac{y+z-x}{x}+2=\frac{z+x-y}{y}+2=\frac{x+y-z}{z}+2\)
\(\Leftrightarrow\frac{x+y+z}{x}=\frac{x+y+z}{y}=\frac{x+y+z}{z}\)
Nếu x+y+z=0 \(\Rightarrow A=\frac{x+y}{y}.\frac{y+z}{z}.\frac{x+z}{x}=\frac{-z}{y}.\frac{-x}{z}.\frac{-y}{x}=-1\)Nếu x+y+z khác 0 => \(x=y=z\)Thay vào A được : \(A=\left(1+1\right)\cdot\left(1+1\right).\left(1+1\right)=8\)